Poly(butylene succinate-co-adipate)/poly(hydroxybutyrate) blend films and their thermal, mechanical and gas barrier properties. Issue 3 (August 2022) - Luoma, Enni; Rokkonen, Teijo; Tribot, Amélie; Nättinen, Kalle; Lahtinen, Jussi
Depleting fossil resources and plastic pollution have generated an increasing demand for development of renewable and biodegradable polymers. Among other applications, packaging films are at the forefront of the scene. Poly(butylene succinate-co-adipate) (PBSA) is an interesting biopolymer due to its flexibility and good processability. However, its poor barrier properties limit the range of applications. On the contrary, poly(hydroxybutyrate) (PHB) biopolymer reveals good barrier performance, as well as stiffness and fast biodegradation rate. However, PHB drawbacks are its brittleness and difficult processability. By physical blending approach, a solution was delivered to overcome the shortcomings of these biopolymers, resulting in tailored properties of the films. PHB improved barrier performance of the blend film while flexible PBSA contributed to easier processability and better ductility. In this study, biobased and biodegradable blend films were produced in pilot-scale. The effects of PBSA/PHB blending were extensively studied by tensile testing, water and oxygen barrier testing, and thermal analysis. PBSA/PHB blend films exhibited improved Young's modulus in comparison to neat PBSA. With 50 wt% PHB content, modulus of blend film was increased by 554% compared to pure PBSA film. The ductility of blend films decreased as a function of PHB content, becoming completely brittle at 50 wt%. It was found that barrier properties of PBSA/PHB films improved in comparison to neat PBSA. Oxygen transmission test results showed that oxygen permeability decreased as a function of PHB content. Similar trend was observed with water vapour permeation properties.